PERAN PERPUSTAKAAN TERHADAP PENINGKATAN LITERASI INFORMASI MAHASISWA PROGRAM STUDI KEPERAWATAN PEKALONGAN POLTEKKES KEMENKES SEMARANG DI MASA PANDEMI COVID-19 - Setyowati, Sri; Edi, Wijanarko; Darwoto, Darwoto; Dewi, Nivea Paula (Poltekkes Kemenkes Semarang, 2021)
Background and Research Objectives - In Indonesia, information literacy coincides with the phenomenon of illiteracy and low reading interest. The library as an educational institution plays an important role in increasing information literacy in the world of education. Likewise, libraries in Higher Education are very important in supporting the Tri Dharma of Higher Education. This study aims to determine the role of the Pekalongan Nursing Study Program Library in increasing information literacy, as well as to determine the benefits of information literacy for students during the Covid-19 pandemic.Methodology - This research is descriptive quantitative in nature. A total of 70 respondentswere recruited by means of accidental sampling to measure the role of the library. The questionnaire was made referring to library standards and was developed based on the Likert scale. After the data is collected, it is processed and presented in tables and graphs. Furthermore, the data are descriptively categorized into interval scales, namely: 1) very good (3.28-4.03), 2) good (2.52-3.27), 3)less good (1.76-2, 51), 4) not good (1.00-1.75).Research Results - The results of the research that have been achieved with respondents, namely students of the Poltekkes of the Ministry of Health in Semarang, level 2 and level 3 of the Pekalongan Nursing Study Program, which have been carried out since June 2020, show that the role of libraries in student information literacy during the Covid-19 pandemic in Pekalongan Nursing Study Program, Poltekkes Ministry of Health Semarang with